Water quality assessment after modernization of the technological system in the water treatment plant in Drzenin (Poland) - Jakubaszek, Anita; Wilczyński, Jarosław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article assesses the physical and chemical parameters of drinking water before and after the modernization of the technological system of water treatment station in Drzenin, Poland. The extension and modernization of the existing installation was necessary due to the poor technical condition of the devices, increasing demand for water in recent years and the periodic exceeding of the permissible values of water quality indicators.
Keywords: groundwaters; groundwater treated water; water quality; modernization; water treatment stations; wody gruntowe; uzdatnione wody gruntowe; jakość wody; modernizacja; stacje uzdatniania wody